13.8k views
5 votes
Solve the equation: -68 = 5y - 3

2 Answers

1 vote

Answer:

-13

Explanation:

-68 = 5y-3 First you move the -3 by adding 3 to both sides to get -65 =5y

Then you divide 5 by both sides to get y=-13

User Jan Schultke
by
4.8k points
3 votes

Answer:

y = -13

General Formulas and Concepts:

Pre-Algebra

  • Order of Operations: BPEMDAS
  • Equality Properties

Explanation:

Step 1: Define equation

-68 = 5y - 3

Step 2: Solve for y

  1. Add 3 to both sides: -65 = 5y
  2. Divide both sides by 5: -13 = y
  3. Rewrite: y = -13

Step 3: Check

Plug in y to verify it's a solution.

  1. Substitute: -68 = 5(-13) - 3
  2. Multiply: -68 = -65 - 3
  3. Subtract: -68 = -68

And we have our final answer!

User Gunner
by
4.3k points